Metabolism, Function, Molecular Mechanism, and Application of Carotenoids in Coloration of Aquatic Animals - Yongguan Liao; Bo Zhang; Deshou Wang; Dongneng Jiang; Chunhua Zhu; Siping Deng; Huapu Chen; Guangli Li; Hongjuan Shi (Reviews in Aquaculture, 2025)
Among vertebrates, aquatic animals have a wide variety of body color. Yellow and red coloration, an important economic trait of aquatic animals, plays pivotal roles in ornamental value and consumption. Fish possess the most chromatophore types in vertebrates, and carotenoids primarily contribute to erythrophore and xanthophore pigmentation. Carotenoid metabolism and regulation of chromatophore development have long been a focus of selective breeding programs in fish. In crustaceans, carotenoids have been proven to be involved in enhancing coloration. However, the carotenoid requirements vary among different aquatic animals. The metabolic pathways in vivo and biochemical processes have not been well summarized. Thus, in this review, we introduced various types of carotenoids and their metabolic pathways in different aquatic species and described a similar mechanism of ketocarotenoid biosynthesis in fish and birds. We have focused on carotenoid metabolism processes and several significant genes involved in the coloration of vertebrates, such as scavenger receptors, apolipoproteins, ketolases, and β‐carotene oxygenase, and their applications in aquaculture. In addition, we also summarized the current problems of carotenoid addition in diets and emphasized the importance of aquatic breeding and molecular biotechnology in carotenoid coloration and ornamental fish breeding. Finally, we provided our perspectives on fish carotenoid pigmentation research and the aquatic industry. This review will enhance our understanding of fish carotenoid metabolism as well as provide deeper insights into the molecular mechanism of fish muscle and skin pigmentation. It will benefit the production of feed additives and selective breeding for ornamental aquatic animals.